Nitrogen-Doped Porous Waste Biomass as a Sustainable Adsorbent for CO2 Capture: The Influence of Preparation Conditions - Peres, Christiano B. [UNESP]; Morais, Leandro C. [UNESP]; Resende, Pedro R. (MDPI, 2025)
In the context of global warming, technologies and studies aimed at mitigating carbon dioxide (CO2) have become increasingly relevant. One such technology is CO2 capture by activated and functionalized N-doped carbon from biomasses. This paper explores the ways to find the optimal CO2 adsorption conditions, based on the carbonization temperature, impregnation rate, and preparation method, considering four different preparation routes in activated and functionalized carbon-N (PCs) of banana peel biomass residues. PCs were produced and chemically activated by K2C2O4 and H2O and functionalized by ethylenediamine (EDA). Carbon dioxide capture was investigated using functional density theory (DFT). Nitrogen (N) doping was confirmed by X-ray photoelectron spectroscopy (XPS), while the thermal characteristics were examined by thermogravimetric analysis (TGA). Surface morphology was examined by scanning electron microscopy (SEM) with energy dispersive X-ray (EDX) detection, and surface functional groups were characterized using Fourier-transform infrared (FTIR) spectroscopy. In addition, the inorganic components were characterized by X-ray diffraction (XRD). The best performance of CO2 adsorption of 1.69 mmol/g was achieved at 0 °C and 1 bar over the adsorbent synthesized at 600 °C with 60 min residence time, a 1:1 degree of impregnation, and a dry preparation method (single-stage preparation). This work presents as a great innovation the use of biomass as a raw material in the adsorption of the main greenhouse gases, using easy and accessible products.
Keywords: CO2 capture; nitrogen-doped; porous carbon; residual biomass